The American Connection: Jean-Christophe Averty and his U.S. TV Contemporaries - Spigel, Lynn (Cinémas)

(untitled) (Cinémas, 2016)
This essay explores the television productions of Ernie Kovacs and Charles and Ray Eames, analyzing their pioneering audio-visual experiments in the American network broadcast system of the mid-century period. It examines how their work with TV graphics, montage, collage, sound, video tricks and special effects relates to Jean Christophe Averty’s work in French TV in the same period. It explores the “experimental spirit” across the Atlantic before the rise of video art per se, demonstrating how all of these early TV artists challenged dominant conceptions of what TV should be in their respective national and industrial contexts. Finally, it calls for more historical research on and theoretical inquiry into the complex relationships between art, design and commercial TV at mid-century.